Eriophyoid mites (Acari: Prostigmata: Eriophyoidea) from Turkey: description of five new species - Kiedrowicz, Agnieszka; Denizhan, Evsel; Bromberek, Klaudia; Szydło, Wiktoria; Skoracka, Anna (Zootaxa, 2016)
Five new eriophyoid mite species (Eriophyidae) from Turkey are described and illustrated in this paper: Aceria vanensis n. sp., Aceria onosmae n. sp., Aculus lydii n. sp., Aculus gebeliae n. sp. and Aculus spectabilis n. sp.. The descriptions are based on the morphology of females collected from weedy plants, respectively: Amaranthus retroflexus L. (Amaranthaceae), Onosma isauricum Boiss. et Heldr. (Boraginaceae), Hypericum lydium Boiss. (Hypericaceae), Lotus gebelia Vent. (Fabaceae) and Stachys spectabilis Choisy ex DC. (Lamiaceae). The new species were found to be vagrant on their host plants with no visible damage symptoms observed.